Evaluation of biocontrol agents for the management of sorghum anthracnose caused by Colletotrichum sublineola - Zhang, Ji-Wei; Han, Jun-Ru; Zhao, Fei-Fei; Huang, Xi-Rong; Hu, Jin-Ling; Li, Jin-Yang; Zhu, Kai; Mao, Lang; Li, Zi-Han; Xia, Jing-Yang; Su, Jie-Ting; Liang, Ze-Hua; et al. (Frontiers in Plant Science, 2025)
Sorghum anthracnose, caused by Colletotrichum sublineola, poses a severe threat to global sorghum production. In China, the rising demand for organic sorghum used in Baijiu brewing underscores the urgent need for effective biocontrol agents or microbial formulations, which remain scarce. In this study, we assessed the efficacy of six biofungicides and two microbial agents against sorghum anthracnose. All tested biocontrol agents and microbial inoculants significantly inhibited mycelial growth and spore germination of C. sublineola in vitro. Iron chlorin exhibited the lowest EC50; values for inhibition mycelial growth and spore germination, followed by pterostilbene. In greenhouse trials, Pterostilbene and Iron chlorin significantly reduced disease severity, with control efficacies of 41.3% and 51.7%, respectively, whereas Bacillus subtilis and Trichoderma harzianumachieved higher efficacies of 73.0% and 65.5%, respectively. Field trials conducted at two sites in Southwest China further confirmed pterostilbene as the most effective treatment, followed by B. subtilis. Collectively, our results highlight pterostilbene and B. subtilis as promising biocontrol agents. Their application could reduce reliance on chemical fungicides and mitigate associated environmental risks. These findings provide practical and eco-friendly strategies for anthracnose management, supporting the sustainable cultivation of organic sorghum.